Pengikatan Objek Jaminan Pada Akad Rahn Tasjily Tanah Di Pegadaian Syariah - Ayu Fitri Ningsih; Abdul Mujib (ADILLA : Jurnal Ilmiah Ekonomi Syari'ah, 2024)
The research aims to further analyze the implementation of rahn tasjily land pledge agreements in Sharia pawnshops, especially regarding the collateralization of the security object in rahn tasjily land pledge agreements. The analytical method used was normative juridical legal research through the statute approach (Government Regulation in Lieu of Law or Perppu) and the conceptual approach. The analysis results indicate that implementing rahn tasjily land pledge agreements at Sharia pawnshops begins with the submission of financing applications, a business feasibility analysis, and the collateralization process. The collateralization of the security object in rahn tasjily land pledge agreements involves imposing a mortgage right, with the process limited to the SKMHT stage. There is a contradiction between the SKMHT mentioned in the DSN-MUI fatwa on rahn tasjily pledge as collateral for financing settlement and the Mortgage Law, which states that SKMHT is only the authority to impose mortgage rights. SKMHT is not considered as collateral because it lacks guaranteeing power. Therefore, there is no binding security in rahn tasjily land pledge agreements at Sharia pawnshops.